EMANATION THERMAL ANALYSIS OF NATURAL AND CHEMICALLY-MODIFIED VERMICULITE - Poyato J.; Pérez-Maqueda L.A.; Justo A.; Balek V. (My University, 2002)
Emanation thermal analysis (ETA), based on radon release measurements from previously labeled samples, was used for the first time in the characterization of the thermal behavior of natural Mg2+-vermiculite (Santa Olalla, Huelva, Spain) and of Na+- and NH+-exchanged vermiculite samples. In addition, vermiculite samples subjected to a chemical treatment with an aqueous solution of (NH4)2SiF6 and partially or totally re-saturated with Na+ ions were also investigated by ETA. The ETA results of natural Mg2+-vermiculite, Na+-vermiculite and NH4+-vermiculite gave supplementary information about microstructure changes of the samples observed under dynamic heating conditions. The method has proved to be very useful for characterization of microstructure changes due to modification in the interlayer space of samples during the heat treatment. The crystallization of vermiculite into new phases, such as enstatite (for NH4+-vermiculite and Mg2+-vermiculite) and forsterite (for Na+-vermiculite) was also observed by ETA.
Keywords: DTA; Emanation Thermal Analysis; Interlayer Space; Microstructure; Thermogravimetry; Vermiculite